Pengembangan Buku Panduan Penggunaan Aplikasi Resertifikasi Kompetensi untuk Karyawan Perhimpunan Dokter Sepsialis Penyakit Dalam Seluruh Indonesia - Puguh Septiadi Nugroho; RA Hirmana Wargahadibrata; Erry Utomo (Jurnal Pembelajaran Inovatif, 2019)
This development research aims to produce a print media in the form of a guidebook to use of the Application “Resertifikasi Kompetensi KIPD”. This guidelines is meant to be used by employees Branch of PAPDI in Indonesia. This development research is referring to Rowntree’s model that consists of three major stages; planning; preparation of writing; writing and editing. The evaluation on this development research was conducted through expert review and one-to-one evaluation. The evaluation involving one subject matter expert, one media expert, and five users. The average value obtainded from the expert review by the subject matter expert was 3,46 overall excellent. The average value obtainded from the expert review by the media expert was 2,56 overall good. In one-to-one evaluation, obtained the average score 3,4 which signifies the overall guidance is excellent and can be used to guide the employees Branch of PAPDI to using the Application “Resertifikasi Kompetensi KIPD” correctly and precisely.